Modelo preditivo para intervenção coronária percutânea, em pacientes com infarto agudo do miocárdio, com supradesnivelamento do seguimento ST - Pereira, Natalia Herculano (2014)
Percutaneous coronary intervention (PCI) is today the most commonly employed revascularization modality in the treatment of acute myocardial infarction with non ST segment (IAMCST). In the specialized literature there are few studies on the association between risk factors and the ICP. Therefore, the goal of this research was to design a predictive model to assist the decision of performing an ICP, from the identification of the existence and of the hierarchy of risk factors that make up the profile of adult individuals infracted. This is a cross-sectional study, descriptive and inferential statistics, quantitative approach. The data were collected in the State's Heart Institute (INCOR) in the city of João Pessoa, in the period from January to September 2013. Were included in the survey individuals infracted confirmed by ECG and laboratory examination (positive Troponin). The logistic regression model was used to obtain and adequacy of the predictive model and all the data were analyzed in the statistical software R ®, version 3.0.2. 100 patients participated in the study with IAMCST, of whom 55% underwent catheterization and 45% angioplasty. The performed the catheterization, the median age was 63.1 years (± 10.45 years), and 56% are male and 44% female. In relation to undergoing angioplasty, the average age was of 64.22 years (± 12.51 years), with 53 percent men and 47 percent women. Has been identified as risk factors for the ICP, the individual with a history of cardiac catheterization (OR = 6.08); family history of angioplasty (OR = 4.52) and body mass index (BMI) and the waist-hip ratio (WHR) high with, OR = 1.61 and OR = 1.37, respectively. We conclude from the data processed in our research that an individual chest pain which gives entry to the INCOR-PB and presents history of cardiac catheterization, angioplasty, family history of BMI and WHR high, must be forwarded immediately to the hemodynamic room because presents 88.9% chance of needing an ICP. This study suggests and reinforces the importance and necessity of further studies evaluating the risk factors associated with ICP and not just the profile of patients who make up this group, to the populations of different Brazilian regions, in order to guide and guide to medical practice, reducing mortality and spending on unnecessary procedures.